Targeting the double-edged sword: cytokines in the pathogenesis and treatment of autoimmune diseases - Fatima Dandash; Zahraa Salhab; Rawan Issa; Zeinab Al Dirani; Mariam Hamze; Gabriel Fares; Fatima Berro; Fatima Shaalan; Ali Hamade; Makram Merimi; Mehdi Najar; Rayan Dakroub; et al. (Inflammopharmacology, 2025)

Synthesis of adamantane-monoterpene conjugates with 1,3,4-thiadiazol-2(3H)-imine linker and evaluation of their inhibitory activity against TDP1 - Aldar A. Munkuev; Alexandra L. Zakharenko; Tatyana E. Kornienko; Nadezhda S. Dyrkheeva; Ekaterina S. Ilina; Evgeniy V. Suslov; Fatima Issa; Chigozie Achara; Jóhannes Reynisson; Konstantin P. Volcho; Nariman F. Salakhutdinov; Olga I. Lavrik (Medicinal Chemistry Research, 2024)

Inhibition of p90 ribosomal S6 kinase attenuates cell migration and proliferation of the human lung adenocarcinoma through phospho-GSK-3β and osteopontin - Nabeel Abdulrahman; Maiy Jaballah; Noufira Poomakkoth; Sadaf Riaz; Somaia Abdelaziz; Aya Issa; Fatima Mraiche (Molecular and Cellular Biochemistry, 2016)

Response of Quinoa to Different Water Management Strategies: Field Experiments and Saltmed Model Application Results - Rachid Fghire; Said Wahbi; Fatima Anaya; Oudou Issa Ali; Ouafae Benlhabib; Ragab Ragab (Irrigation and Drainage, 2015)
Given the current water shortage in North Africa, improving water management to produce more crop per drop is vital. In addition, the introduction of drought‐tolerant, less water‐consuming crops such as quinoa is of great interest. To understand the response of quinoa to water stress in terms of biomass and grain yield under various irrigation management strategies, the SALTMED model was employed using field measurements during the cropping seasons of 2011 and 2012 at a site in the Marrakech region, south Morocco. Quinoa showed its ability to grow in the south of Morocco and give a good yield under full irrigation. However, the experimental and modelling results showed that under rainfed and deficit irrigation, the grain yield was lower than under the full irrigation treatment and was dependent on water deficit level. The study revealed that a reasonable grain yield of quinoa can only be obtained if it was subjected to moderate water stress conditions. The results indicated that the SALTMED model is able to simulate the quinoa biomass and grain yield under various water deficit levels and that the model can be used in the evaluation of different irrigation strategies. Copyright © 2015 John Wiley & Sons, Ltd.